Equity research: an evaluation of EDP´s tender offer over EDP Renováveis - Heitor, Gonçalo Manuel Martinho (2018)
The increasing cost competitiveness of renewable technologies (mainly wind power and solar PV), the continuous increase in global electricity demand and strict government policies towards the decarbonisation of the economy are some of the main challenges and growth opportunities that have been increasingly transforming the renewable energy industry. One of the companies in the front row of this ongoing revolution is EDP Renováveis, focused exclusively on the generation of energy from renewable sources, primarily wind onshore. Hence, to benefit even more from the attractive growth of EDPR, its major shareholder (EDP - Energias de Portugal) launched on 27 March 2017 a tender offer to buy-back the 22.47% of share capital it did not hold in the subsidiary, at a price of €6.75 per share. This dissertation presents, as of 31 March 2017, a comprehensive analysis and consequent estimation of the fair value of EDP Renováveis, by targeting a price for the year-end 2017. Consequently, it allowed for the fair evaluation of EDP’s offer and to answer whether minority shareholders should be willing to accept it or not. Accordingly, a sum-of-the-parts DCF valuation derives a target price of €7.83 per share, i.e., a 13% upside, which clearly indicates that the price offered by EDP did not truthfully reflected the fundamental value of the company and its potential growth. Overall, the positive historical performance and low-risk approach to attractive markets, such as the United States, are fundamental to support a buy recommendation, considering the market ight be undervaluing the stock